Diabetes in Patients With Pancreatic Neuroendocrine Neoplasms - Zhuge, Xiaoling; Wang, Yajie; Chen, Xiao; Guo, Chuangen (Frontiers in Endocrinology, 2020)
Objective Diabetes mellitus (DM) is probably a risk factor for pancreatic neuroendocrine neoplasms (PNENs). However, the prevalence of DM in PNEN patients remains inconclusive. In the present study we observed the prevalence of DM and possible risk factors in PNEN patients. Methods After excluding those with insulinoma, a total of 197 patients with PNENs were included. The demographic data, pathological characteristics and data of blood biochemical tests were recorded. DM was considered if there was evidence of a fasting plasma glucose level of ≥ 7.0 mmol/L or a 2-h plasma glucose level of ≥ 11.1 mmol/L, or a history of DM at the time of PNEN diagnosis. Impaired fasting glucose was considered if fasting plasma glucose level was between 6.1 and 7.0 mmol/L. Results The prevalence of DM, new-onset DM, and impaired fasting glucose were 17.26%, 9.14%, and 7.1%, respectively. The prevalence of DM was 26.0% in patients ≥ 60 years old (19/73) and 12.1% in patients < 60 years old. Multivariable logistic regression analysis demonstrated that age, tumor size and nerve invasion were independent risk factors for DM and impaired fasting glucose + DM (p < 0.05). Age, organs and nerve invasion were independent risk factors for impaired fasting glucose. Low high-density lipoprotein (HDL) was also a risk factor for incident of DM (OR = 0.15, 95%CI: 0.03-0.66). G2/G3 was an independent risk factor for DM in women. Conclusion Our data shows that the prevalence of DM is 17.26% in patients with PNENs and is 26.0% in patients ≥ 60 years of age after excluding insulinoma. Age, nerve invasion, tumor size, and HDL are risk factors for DM in PNEN patients.